Two new species of Marphysa (Annelida, Eunicidae) from southern Australia. - Lavesque, Nicolas; Zanol, Joana; Daffe, Guillemine; Flaxman, Beth; Hutchings, Pat (Zootaxa, 2023)
Two new species of Marphysa Quatrefages, 1866 are described from the southeast coast of Australia. With the presence of only compound spinigers and the branchiae present over many chaetigers, Marphysa baudini n. sp. belongs to the Sanguinea-group. This species has ventral cirri with an inflated base and digitiform tip and thick and wide anodont pectinate chaetae, with 3–5 internal long and thick teeth. With the presence of only compound falcigers, Marphysa davidattenboroughi n. sp., belongs to the “Aenea-group”. This species is characterised by the presence of a bilobed prostomium, a single pair of pygidial cirri and by the presence of thick, and wide anodont pectinate chaetae with 4–6 long internal and thick teeth.